PENGARUH KONFLIK KERJA DAN STRES KERJA TERHADAP KEPUASAN KERJAâ€ (Studi Pada Karyawan PT. Indah Logistik Cabang Pekanbaru) - Ramadanu, Dwipa; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine how the effects work conflict and work stress on job satisfaction on PT Indah logistic branch of Pekanbaru. The population in this study were employees of PT Indah logistic branch of Pekanbaru, the sampling using census method in order to get 63 votes. The data collection of primary data research, using questionnaires as the instrument research and secondary data turned away company archives, data analysis used is by using multiple linear regression, determination test, t test and f SPSS.From the results of data analysis include validity, reliability, and multiple linear regression, the results showed the calculation of the t (5.667)> t table (2,001) and Sig. (0.000) <0.05. This means that variable Work Conflict significant effect on Job satisfaction.And the results showed the calculation of the t (3.881)> t table (2,001) and Sig. (0.000) <0.05. This means that variable significant effect on the Job Stress Job Satisfaction and based on the simultaneous test concluded that the work conflict and work stress together significant effect on employee satisfaction with the influence of 64.3%. Keywords: Work Conflict, Job Stress, Job Satisfaction